2018
DOI: 10.1103/physrevb.98.094415
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and exchange-bias effect at the MnN/Fe interface

Abstract: Based on ab initio calculations and spin dynamics simulations, we perform a detailed study on the magnetic properties of bulk MnN and the MnN/Fe interface. We determine the spin model parameters for the θ-phase of bulk MnN, and we find that the competition between the nearest and the next-nearest-neighbor interactions leads to antiferromagnetic ordering of the Mn spins, in agreement with previous theoretical and experimental results. At the MnN/Fe interface, a sizable Dzyaloshinskii-Moriya interaction appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This decrease is possibly due to desorption of nitrogen from the MnN [16] or an irreversible structural/magnetic transition in the MnN or at the MnN/CoFe interface [7]. The shape of the hysteresis loops as well as the magnitude of the loop shift are in good agreement with recent theoretical investigations by Simon et al [17], albeit for a different ferromagnetic system. As can be seen in Figure 2 the Mn spins in the MnN layer are oriented out-of-plane.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This decrease is possibly due to desorption of nitrogen from the MnN [16] or an irreversible structural/magnetic transition in the MnN or at the MnN/CoFe interface [7]. The shape of the hysteresis loops as well as the magnitude of the loop shift are in good agreement with recent theoretical investigations by Simon et al [17], albeit for a different ferromagnetic system. As can be seen in Figure 2 the Mn spins in the MnN layer are oriented out-of-plane.…”
Section: Resultssupporting
confidence: 88%
“…At the interface between the F and AF layers there is ferromagnetic coupling with the spins preferring to lie in a direction parallel to the plane of the interface. This leads to a twisted spin structure across the interface [17]. The value of the anisotropy constant varied from sample to sample which is shown in the data in Figure 8 due to the proportionality of <TB>, i.e.…”
Section: Resultsmentioning
confidence: 93%
“…The Curie temperature for ferromagnetic ground states was obtained from the magnetization curve M 2 (T) resulting from finite temperature atomistic spin-dynamics simulations [22], a recent example using this method is reported in Ref. [23].…”
Section: Calculationsmentioning
confidence: 99%
“…Materials 2022, 15, x FOR PEER REVIEW 4 of 14 atomistic spin-dynamics simulations [22], a recent example using this method is reported in Ref. [23].…”
Section: Growth and Crystallographic Structurementioning
confidence: 99%
“…In both cases, the Mn atoms had a magnetic moment of 3.3 µ B at room temperature. More recently, a theoretical study has suggested that the spin alignment is along the c-axis [16]. The authors found that the first nearest-neighbor isotropic exchange interactions are AF, while the second nearest-neighbor interactions are strongly ferromagnetic.…”
Section: Manganese Nitride: the Materialsmentioning
confidence: 99%